Pendampingan Manajemen Pengelolaan Dana Desa di Desa Benan Kecamatan Katang Bidare, Kabupaten Lingga - Oksep Adhayanto; Nazaki Nazaki; Nanik Rahmawati; Yudhanto Satyagraha A; Nikodemus Niko (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This article discusses the mentoring of village fund management in Benan Village, Katang Bidare Subdistrict, Lingga Regency. The village fund management mentoring is carried out by the community service team of the Faculty of Social and Political Sciences at Raja Ali Haji Maritime University as part of the higher education tridharma. The purpose of this activity is to describe the mentoring process conducted by the community service team in Benan Village, with a focus on efforts to improve the efficiency, accountability, and transparency of village fund management. The implementation method of this community service is through socialization and lectures. The results of this community service show that the mentoring of village fund management in Benan Village has a positive impact on improving the management of village funds. The mentoring is done through socialization and technical guidance. Based on the results of this activity, the community service team identifies some challenges faced in village fund management mentoring, including uncertainty in mentoring resources and coordination among related institutions.